Integrated Coagulation-Adsorption-Filtration-Ceramic Membrane System for the Treatment of Songket Dyeing Wastewater - Rizki Rinaldi; Muhammad Said; Desnelli Desnelli (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
This study investigated an integrated treatment system combining coagulation, adsorption, filtration, and ceramic membrane processes for songket dyeing wastewater. Textile wastewater is characterized by high color intensity, suspended solids, and organic loads, which can cause serious environmental impacts if discharged without adequate treatment. Coagulation using aluminum sulfate effectively destabilizes colloidal particles, followed by adsorption with activated carbon to remove dissolved dyes and organic compounds. Multimedia filtration and ceramic membrane filtration further enhance pollutant removal through physical separation mechanisms. The integrated system successfully achieved color reduction from 976.5 Pt-Co to 10.6 Pt-Co, TSS reduction exceeding 98%, and COD reduction above 93%, in accordance with Indonesian wastewater discharge standards for the textile industry (KLHK, 2016).Keywords: Songket Wastewater, Coagulation, Adsorption, Filtration, Ceramic Membrane